Probing of Brain States in Real-Time: Introducing the ConSole Environment - Hartmann, Thomas; Schulz, Hannah; Weisz, Nathan (Frontiers in Psychology, 2011)
Recent years have seen huge advancements in the methods available and used in neuroscience employing EEG or MEG. However, the standard approach is to average a large number of trials for experimentally defined conditions in order to reduce intertrial-variability, i.e. treating it as a source of "noise". Yet it is now more and more accepted that trial-to-trial fluctuations bear functional significance, reflecting fluctuations of "brain states" that predispose perception and action. Such effects are often revealed in a pre-stimulus period, when comparing response variability to an invariant stimulus. However such offline analyses are disadvantageous as they are correlational by drawing conclusions in a posthoc-manner and stimulus presentation is random with respect to the feature of interest. A more direct test is to trigger stimulus presentation when the relevant feature is present. The current paper introduces ConSole (CONstance System for OnLine Eeg), a software package capable of analyzing ongoing EEG / MEG in real-time and presenting auditory and visual stimuli via internal routines. Stimulation via external devices (e.g. TMS) or third-party software (e.g. Psyscope X) is possible by sending TTL-triggers. With ConSole it is thus possible to target the stimulation at specific brain-states. In contrast to many available applications, ConSole is open-source. Its modular design enhances the power of the software as it can be easily adapted to new challenges and writing new experiments is an easy task. ConSole is already pre-equipped with modules performing standard signal processing steps. The software is also independent from the EEG / MEG system, as long as a driver can be written (currently 2 EEG systems are supported). Besides a general introduction, we present benchmark data regarding performance and validity of the calculations used, as well as three example applications of ConSole in different settings. ConSole can be downloaded at: http://console-kn.sf.net.